The innovative business model of Xiaoxiandun Bird’s Nest - Qiao, Han, (SAGE Business cases., 2024)
In 2013, the edible bird’s nest industry outfaced chaotic market competition, poor customer awareness, a lack of trust, and a lack of strong branding during its infancy, thereby resulting in development opportunities for new categories and brands. Xiaoxiandun Freshly Stewed Edible Bird’s Nest ("XXD") foresaw the strategic direction and emerged into prominence in the industry within less than six years. Moreover, XXD solved the pain points of the industry and consumers, developed the category of "freshly stewed bird’s nests," introduced a customer-to-manufacturer (C2M) model, and directly reached consumers from the factory through value creation. Furthermore, XXD achieved rapid growth and became a leader in the industry through its innovative business model. This case focused on the development of XXD, analyzed its business model, and described ways in which the company discovered and met new consumer demand as well as built a new supply chain system through innovation. However, XXD, which began with online sales, faced back-and-forth attacks from competitors. Traditional bird’s nest giants launched online sales, intensifying online traffic and competition. Accordingly, XXD considered opening brick-and-mortar stores to further expand the brand’s influence and increase its competitiveness, which would require a huge investment of resources. However, no consensus was reached among the founders of XXD despite several discussions within the company.